2013
DOI: 10.5012/bkcs.2013.34.8.2413
|View full text |Cite
|
Sign up to set email alerts
|

1D Proton NMR Spectroscopic Determination of Ethanol and Ethyl Glucuronide in Human Urine

Abstract: Forensic and legal medicine require reliable data to indicate excessive alcohol consumption. Ethanol is oxidatively metabolized to acetate by alcohol dehydrogenase and non-oxidatively metabolized to ethyl glucuronide (EtG), ethyl sulfate (EtS), phosphatidylethanol, or fatty acid ethyl esters (FAEE). Oxidative metabolism is too rapid to provide biomarkers for the detection of ethanol ingestion. However, the nonoxidative metabolite EtG is a useful biomarker because it is stable, non-volatile, water soluble, high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
(7 reference statements)
0
3
0
Order By: Relevance
“…To better understand why module #240 correlates more strongly to the alcohol consumption biomarker while being a worse match to ethanol than module #57 (Figure 3), we studied whether any of its features point to other compounds related to ethanol metabolism. Indeed, we found that this module contains three (Nicholas et al 2006) and more recently in human urine of alcohol drinkers (Kim et al 2013) . To confirm EtG as a possible match for ISA module #240, we added its features as extracted from (Nicholas et al 2006) to the metabomatching library manually, since EtG had no entry in UMDB.…”
Section: Metabolite Concentration Pseudo-quantification With Nmr Featmentioning
confidence: 71%
“…To better understand why module #240 correlates more strongly to the alcohol consumption biomarker while being a worse match to ethanol than module #57 (Figure 3), we studied whether any of its features point to other compounds related to ethanol metabolism. Indeed, we found that this module contains three (Nicholas et al 2006) and more recently in human urine of alcohol drinkers (Kim et al 2013) . To confirm EtG as a possible match for ISA module #240, we added its features as extracted from (Nicholas et al 2006) to the metabomatching library manually, since EtG had no entry in UMDB.…”
Section: Metabolite Concentration Pseudo-quantification With Nmr Featmentioning
confidence: 71%
“…Indeed, we found that this module contains three features, at 1.26, 3.52, and 4.47 ppm, that individually correlate more strongly to CDT (0.40 [0.34, 0.45], 0.29 [0.23, 0.35], 0.33 [0.27, 0.39], respectively) than the features mapping to ethanol. Interestingly, these features appeared to be close to those of ethyl glucuronide (EtG), a direct product of ethanol nonoxidative metabolism by conjugation with uridine diphosphate (UDP)-glucuronic acid, which had previously been detected in 1 H NMR spectra of liver extracts and more recently in human urine of alcohol drinkers . To confirm EtG as a possible match for ISA module #240, we added its features as extracted from Nicholas et al to the metabomatching library manually, since EtG had no entry in UMDB.…”
Section: Analysis and Resultsmentioning
confidence: 99%
“…Inhaled toluene is metabolized to hippuric acid in the liver and excreted in the urine. In another example, Dr. Kim found that the biomarker ethyl glucuronide could be used instead of ethanol as an indicator of alcohol consumption (Kim et al 2013a). Dr. Kim applied NMR-based metabolomics to tests of environmental toxicity and successfully found many biomarkers in zebrafish for each chemical treatment tested, including organic solvents, pesticides, and medicines (Yoon et al 2013).…”
mentioning
confidence: 99%